La relation vitesse-precision au tir debout en biathlon - Grebot, C.; Groslambert, A.; Rouillon, J. D. (Science & Sports, 2002)
Introduction - The aim of this study was to investigate the relationship between velocity and accuracy in standing shooting in eight biathletes of national level.